Resilience in the Face of Disability - GarcÃƒÂa, Bibian Bibeca Bumbila; Zambrano, Ruth Leonor Bergmann; Bravo, MarÃƒÂa Gabriela Palma (International Research Journal of Management, IT & Social Sciences, 2018)
The objective of the work is to identify the most preeminent elements of resilience in the face of disability at the Technical University of ManabÃ. To do this, a wide-ranging exploration and bibliographical study was carried out, which allowed us to return to the criteria addressed by several authors recognized internationally in the study of resilience and especially those of the Latin American area. The work deals with contemporary contextual aspects that may be favorable to the psychosocial approach to resilience. The article is based on research based on the qualitative interpretative paradigm. The theoretical referents were consigned from the bibliographic review, to compare them with the empirical phase that allowed interpreting the individual representations of disabled youth about resilience. The results of the research show that resilience is widely known, although an important bias is maintained in its representation related to a more individual than the social view, which could limit its influence as a pedagogical factor.